TRANSFORMASI SPIRITUAL DARI TRADISI KE MODERNITAS: SYEKH AKBAR MUHAMMAD FATHURAHMAN DAN PEMBARUAN TAREKAT IDRISIYYAH DI ERA MODERN - Muhamad Yusuf Sidiq Yusuf (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2025)
This research examines the life journey and leadership of Sheikh Muhammad Fathurrahman as Mursyid of Tarekat Al-Idrisiyyah. Since childhood, he has spent his life in Islamic boarding schools, making him closer to the Islamic educational environment than his own family. His leadership process cannot be separated from the role and guidance of previous Mursyid teachers, especially Sheikh Muhammad Dahlan and Sheikh Al-Akbar Muhyiddin. Through various tests and mandates given, he developed into a mature leader, with a main focus on reform (tajdid) in the fields of Tawhid, Fiqh, and Sufism. This research describes how his leadership was formed through a long spiritual and intellectual journey. The research results show that Sheikh Muhammad Fathurrahman's leadership is based on a combination of formal education, Islamic boarding school experience, and closeness to previous Murshids, which made him a central figure in the development of da'wah and tarekat in Indonesia.